Examining affective structure in chickens: valence, intensity, persistence and generalization measured using a Conditioned Place Preference Test - Paul, Elizabeth S. (Appl Anim Behav Sci, 2018)
When measuring animals’ valenced behavioural responses to stimuli, the Conditioned Place Preference (CPP) test goes a step further than many approach-based and avoidance-based tests by establishing whether a learned preference for, or aversion to, the location in which the stimulus was encountered can be generated. We designed a novel, four-chambered CPP test to extend the capability of the usual CPP paradigm to provide information on four key features of animals’ affective responses: valence, scale, persistence and generalization. Using this test, we investigated the affective responses of domestic chickens (Gallus gallus domesticus) to four potentially aversive stimuli: 1. Puffs of air; 2. Sight of (robotic) snake; 3. Sprays of water; 4. Sound of conspecific alarm calls. We found conditioned avoidance of locations associated with the air puffs and water sprays (Friedman’s χ(2)((3)) = 13.323 p > .005; χ(2)((3)) = 14.235 p > .005), but not with the snake and alarm calls. The scale of the learned avoidance was similar for the air puff and water spray stimuli, but persistence and generalization differed. We conclude that the four chambered CPP test can have a valuable role to play in making multi-feature measurements of stimulus-generated affective responses, and we highlight the value of such measurements for improving our understanding of the structure of affect in chickens and other animals.